Unlocking imagination: exploring the creative potential in autism spectrum disorder / Izza Syahida Abdul Karim, Noor Faaizah Wan Omar and Azlyn Ahmad Zawawi - Abdul Karim, Izza Syahida; Wan Omar, Wan Noor Faaizah; Ahmad Zawawi, Azlyn (Universiti Teknologi MARA, Kedah, 2024)
Autism spectrum disorder or ASD is a developmental disability caused by differences in the brain that may behave, interact, communicate, and learn in a way differently from most people (Centers for Disease Control and Prevention, 2022), affecting approximately one percent of the worldwide population. As inspired by one of Dr. Temple Grandin’s quotes in her book, as a Person with Autism (PWA) herself, “Different, not less”. The autism community promotes this phrase as a well-recognized motto for what autistic people can offer to the world. In Malaysia, as well as in many other countries, there is a growing recognition of the unique strengths and potential of autistic individuals.